Annickia polycarpa extract attenuates inflammation, neutrophil recruitment, and colon damage during colitis - Lartey, N.L.; Vargas-Robles, H.; Guerrero-Fonseca, I.M.; Nava, P.; Kumatia, E.K.; Ocloo, A.; Schnoor, M. (Immunology Letters, 2022)
Inflammatory bowel diseases (IBD) including Crohn’s disease (CD) and ulcerative colitis (UC) are complex inflammatory disorders of the digestive tract. Dysfunctional intestinal epithelial barrier, uncontrolled neutrophil recruitment into the colon, and oxidative stress are major features of IBD. IBD cannot be cured, but symptoms can be alleviated with anti-inflammatory drugs, which often show adverse effects. Thus, safer alternative treatment options are needed. Given the known anti-inflammatory properties of Annickia polycarpa extract (APE), we hy pothesized that APE improves the outcome of the inflammatory response during colitis. We assessed APE effects on colon histology, epithelial barrier function and neutrophil recruitment during DSS-induced colitis in mice treated with APE. APE treatment significantly reduced the disease activity index and prevented DSS-induced colon damage as evidenced by reduced colon shortening, ulcerations, crypt dysplasia, edema formation, and leukocyte infiltration. Expression of the pro-inflammatory cytokines TNF-α, IL-6, and IL-1β were significantly diminished in APE-treated mice. Importantly, APE administration reduced neutrophil infiltration into the lamina propria leading to reduced oxidative stress, tight junction disruption and epithelial permeability in the colon. Thus, we propose APE as additional treatment strategy to attenuate colitis symptoms and enhance life quality of individuals with IBD.
Research Article
Keywords: Inflammatory bowel diseases; Ulcerative colitis; Nutritional supplement; E--cadherin; Reactive oxygen species; ZO-1